Tooth impression silicone rubber material and preparation method thereof

By using ternary self-assembled catalysts, the problems of high platinum content and Pt ion release in Karstedt or Speier type platinum catalysts have been solved, achieving the effects of reducing costs and cytotoxicity, and improving catalytic efficiency.

CN121045843APending Publication Date: 2025-12-02LIAONING UPCERA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511369278.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

In existing addition-reaction silicone rubber materials, Karstedt-type or Speier-type platinum catalysts have high platinum content, resulting in high raw material costs and continuous release of Pt ions in saliva after curing, posing a risk of cytotoxicity.

Method used

A ternary self-assembled catalyst is employed, in which a stable ternary network structure is formed through the synergistic effect of Al, Pt, and Ti. This physically isolates Pt and reduces the release of Pt ions. A sol constructed from Al and Ti is used as a support to load Pt, and Pt is covalently connected to the Al-Ti framework, thereby improving catalytic efficiency.

Benefits of technology

While maintaining or shortening the curing time, it significantly reduces Pt ion release, lowers the risk of cytotoxicity, improves catalytic efficiency, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a dental impression silicone rubber material and a preparation method thereof, and relates to the technical field of dental impression materials. The raw materials of the dental impression silicone rubber material comprise a matrix component and a catalytic component in a mass ratio of 1: (0.8-1.2), the catalytic component contains a ternary self-assembly catalyst, and the effective content of Al in the ternary self-assembly catalyst is 500-900 ppm, the effective content of Pt in the ternary self-assembly catalyst is 100-500 ppm, and the effective content of Ti in the ternary self-assembly catalyst is 800-1100 ppm. According to the invention, sol constructed by Al and Ti is used as a carrier to load Pt, so that a stable ternary network structure is formed. Pt is physically isolated in a water environment by the structure, electrons are transferred to Pt through oxygen vacancies, the d-band center is reduced, and the catalytic efficiency is improved. On the premise of maintaining or shortening the curing time, the Pt ion release amount can be remarkably reduced, and the cytotoxicity can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of dental impression materials technology, and more specifically, to a silicone rubber material for dental impressions and its preparation method. Background Technology

[0002] Addition-reactive silicone rubber (vinyl-polydimethylsiloxane + Si–H crosslinking agent) has become the preferred material for precision dental impressions due to its good dimensional stability and pleasant feel. This system generally uses Karstedt-type or Speier-type platinum catalysts (zero-valent Pt colloids or chloroplatinic acid complexes) to achieve rapid room temperature curing.

[0003] However, the aforementioned Karstedt-type or Speier-type platinum catalysts have the following drawbacks: (1) High platinum content: In order to ensure that the clinically operable time is <2min, the amount of Pt used is generally 100-2000 ppm, resulting in high raw material costs.

[0004] (2) Ion release: Residual free Pt after curing 2+ / Pt 4+ It continues to dissolve in saliva and the acidic oral environment, with a cumulative release of >0.5 μg / g over 72 hours. -1 There is a risk of cytotoxicity (ISO 10993-5 Grade 2).

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a silicone rubber material for dental impressions and a method for preparing the same.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a dental impression silicone rubber material, the raw materials of which include a matrix component and a catalytic component in a mass ratio of 1:0.8-1.2, wherein the catalytic component contains a ternary self-assembled catalyst, wherein the effective content of Al in the ternary self-assembled catalyst is 500-900 ppm, the effective content of Pt is 100-500 ppm, and the effective content of Ti is 800-1100 ppm.

[0008] In an optional embodiment, the raw materials of the ternary self-assembled catalyst include an Al source, a Ti source, a Pt source, a coordination modifier, and a solvent. The molar ratio of Al to Ti in the Al source and the Ti source is 1:1-3. The molar ratio of the total molar amount of Al and Ti in the Al source and the Ti source to the molar amount of the coordination modifier is 1:1-3. The molar ratio of Pt in the Pt source to the total molar amount of Al and Ti in the Al source and the Ti source is 1:10-50.

[0009] In an optional embodiment, the Al source includes at least one of aluminum chloride, aluminum nitrate, aluminum sulfate, aluminum oxide, and aluminum alkoxide. And / or, the Ti source includes at least one of titanium chloride, titanium sulfate, titanium oxalate, titanium oxide and titanium alkoxide; And / or, the Pt source includes at least one of platinum chloride, platinum oxide, platinum alkoxide, platinum complex, and platinum sulfate; And / or, the coordination modifier comprises at least one of pyridine, triethylamine, ethylenediamine, hexamethylenetetramine, acetic acid, oxalic acid, benzoic acid, trifluoroacetic acid, ammonium chloride, potassium bromide, sodium iodide, water, methanol, ethylene glycol, acetylacetone, and 8-hydroxyquinoline; And / or, the solvent includes anhydrous ethanol.

[0010] In an optional embodiment, the preparation method of the ternary self-assembled catalyst includes: The Al source and the Ti source are dissolved in the solvent in a molar ratio to form a mixed solution with a concentration of 0.05-0.15 mol / L. The coordination modifier is added in a molar ratio, and the mixture is refluxed at 60-80℃ for 1-3 hours to obtain a pale yellow transparent sol with a pH of 4.2-4.8. The Pt source is dissolved in the solvent to form a Pt source solution with a concentration of 0.01-0.03 mol / L. The Pt source solution is added dropwise to the pale yellow transparent sol and refluxed at 70-90℃ for 3-5 hours. In the later stage of the reaction, the pH rises to 5.5-6.0. The absorption peak at λ=360nm disappears when the sample is monitored by UV-Vis, indicating that the reaction is complete, and the ternary self-assembled catalyst is obtained.

[0011] In an optional embodiment, the raw materials for the ternary self-assembled catalyst further include a surface modifier, and the preparation method of the ternary self-assembled catalyst further includes modifying the ternary self-assembled catalyst with the surface modifier, and then removing the solvent to constant weight. Preferably, the molar amount of the surface modifier is 14-16 times the molar amount of the total metal; Preferably, the surface modifier includes at least one of KH550, KH560, mercaptosilane, tetraethyl orthosilicate, KH-570, and HMDZ.

[0012] In an optional embodiment, the raw materials of the matrix component include, by weight, 80-100 parts of vinyl silicone oil, 8-12 parts of reinforcing agent, 2-4 parts of hydrogen-containing silicone oil, 10-15 parts of filler, and 0.1-0.5 parts of pigment; the raw materials of the catalytic component include, by weight, 80-100 parts of vinyl silicone oil, 8-12 parts of reinforcing agent, 2-4 parts of hydrogen-containing silicone oil, 0.1-0.3 parts of ternary self-assembled catalyst, 10-15 parts of filler, and 0.1-0.5 parts of pigment.

[0013] In an optional embodiment, the viscosity of the vinyl silicone oil in the matrix component and the catalytic component is 1000-10000 mPa·s, preferably 3000-8000 mPa·s, and the vinyl content is 0.02-2 wt.%. And / or, the reinforcing agent in both the matrix component and the catalytic component comprises at least one of methyl vinyl MQ silicone resin and vinyl MQ silicone resin, wherein M is a monofunctional Si-O unit, Q is a tetrafunctional Si-O unit, the M / Q ratio is between 0.8 and 1.2, the viscosity of the reinforcing agent at room temperature is 100-10000 Pa·s, and the vinyl content is 0.1-5 wt.%. And / or, the hydrogen content of the hydrogen-containing silicone oil is 0.1-5 wt%, preferably 0.1-2 wt%; And / or, the filler in the matrix component and the catalyst component is a mixture of silica powder and fumed silica; Preferably, the particle size of the silicon micropowder is 1-10 μm, more preferably 2-6 μm; Preferably, the specific surface area of ​​the fumed silica is greater than 200 mm². 2 / g; Preferably, the mass ratio of the silicon micro powder to the fumed silica is 5-50:1, more preferably 5-30:1; And / or, the pigments in the matrix component and the catalytic component are at least one of iron oxide and titanium dioxide.

[0014] Secondly, the present invention provides a method for preparing a dental impression silicone rubber material as described in any of the foregoing embodiments, comprising: mixing the raw materials of the matrix component to obtain a first mixture; mixing the raw materials of the catalytic component to obtain a second mixture; and mixing the first mixture and the second mixture to obtain the final product.

[0015] In an optional embodiment, mixing the raw materials for the catalytic component includes: First, the ternary self-assembled catalyst and the hydrogen-containing silicone oil are ultrasonically dispersed, followed by vacuum degassing to obtain a catalytic dispersion; then, the catalytic dispersion is mixed with the vinyl silicone oil, reinforcing agent, filler and pigment in the catalytic component. Preferably, the side chain Si-H content of the hydrogen-containing silicone oil is 0.4-0.6 wt%, and the viscosity at 25 °C is 80-120 mPa·s; Preferably, the ultrasonic dispersion power is 500-900W, the dispersion time is 20-60min, and the ultrasonic dispersion is performed using a pulse mode of 4-6s ultrasonic waves followed by 4-6s pauses.

[0016] The present invention has the following beneficial effects: The dental impression silicone rubber material provided by this invention uses a ternary self-assembled catalyst formed by the self-assembly of three metals, Al, Pt, and Ti, as the catalyst component. The synergistic effect of Al, Pt, and Ti enables it to exhibit superior performance compared to single-metal or bimetallic catalysts in selective hydrogenation, CO oxidation, photocatalysis, and electrocatalysis. This invention uses an Al and Ti sol as a support to load Pt, with Pt covalently bonded to the Al-Ti framework, forming a stable ternary network structure. This structure physically isolates Pt in an aqueous environment while simultaneously transferring electrons to Pt through oxygen vacancies, reducing the d-band center and improving catalytic efficiency. This invention can significantly reduce Pt ion release and cytotoxicity while maintaining or shortening the curing time. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0018] This invention provides a silicone rubber material for dental impressions, the raw materials of which include a matrix component and a catalytic component in a mass ratio of 1:0.8-1.2. The matrix component, by weight, comprises 80-100 parts of vinyl silicone oil, 8-12 parts of reinforcing agent, 2-4 parts of hydrogen-containing silicone oil, 10-15 parts of filler, and 0.1-0.5 parts of pigment; the catalytic component, by weight, comprises 80-100 parts of vinyl silicone oil, 8-12 parts of reinforcing agent, 0.1-0.3 parts of ternary self-assembled catalyst, 10-15 parts of filler, and 0.1-0.5 parts of pigment. The vinyl silicone oil in both the matrix and catalytic components has a viscosity of 1000-10000 mPa·s, preferably 3000-8000 mPa·s, and a vinyl content of 0.02-2 wt.%; and / or, the reinforcing agents in both the matrix and catalytic components include at least one of methyl vinyl MQ silicone resin and vinyl MQ silicone resin, wherein M is a monofunctional Si-O unit, Q is a tetrafunctional Si-O unit, the M / Q ratio is between 0.8 and 1.2, the reinforcing agent has a viscosity of 100-10000 Pa·s at room temperature, and a vinyl content of 0.1-5%. wt.%; and / or, the hydrogen content of the hydrogen-containing silicone oil is 0.1-5 wt%, preferably 0.1-2 wt%; and / or, the filler in the matrix component and the catalyst component is a mixture of silica powder and fumed silica; preferably, the particle size of the silica powder is 1-10 μm, preferably 2-6 μm; the specific surface area of ​​the fumed silica is greater than 200 mm². 2 / g; the mass ratio of silica powder to fumed silica is 5-50:1, preferably 5-30:1; and / or, the pigments in the matrix component and the catalytic component are at least one of iron oxide and titanium dioxide.

[0019] This invention uses a ternary self-assembled catalyst as the raw material for the catalytic component, replacing the current Karstedt or Speier type platinum catalyst. The effective content of Al in the ternary self-assembled catalyst of this invention is 500-900 ppm, the effective content of Pt is 100-500 ppm, and the effective content of Ti is 800-1100 ppm.

[0020] The effective contents of Al, Pt, and Ti are calculated based on elemental Al and / or its oxides, Pt and / or its oxides, and Ti and / or its oxides. The effective contents of Al, Pt, and Ti are tested using ICP-OES.

[0021] In this invention, a catalyst formed by the self-assembly of three metals, Al, Pt and Ti, is provided. The synergistic effect of the three metals (electronic effect, structural effect, site synergy) enables it to exhibit superior performance to single metal or bimetallic catalysts in selective hydrogenation, CO oxidation, photocatalysis, electrocatalysis and other fields.

[0022] Specifically, the raw materials for the ternary self-assembled catalyst in this invention include an Al source, a Ti source, a Pt source, a coordination modifier, and a solvent. The molar ratio of Al to Ti in the Al and Ti sources is 1:1-3; the molar ratio of the total molar amount of Al and Ti in the Al and Ti sources to the molar amount of the coordination modifier is 1:1-3; and the molar ratio of Pt in the Pt source to the total molar amount of Al and Ti in the Al and Ti sources is 1:10-50.

[0023] Correspondingly, the preparation methods of ternary self-assembled catalysts include: Al and Ti sources were dissolved in a solvent in a molar ratio to form a mixed solution with a concentration of 0.05-0.15 mol / L. A coordination modifier was added in a molar ratio, and the mixture was refluxed at 60-80℃ for 1-3 hours to obtain a pale yellow transparent sol with a pH of 4.2-4.8. The Pt source was dissolved in a solvent to form a Pt source solution with a concentration of 0.01-0.03 mol / L. The Pt source solution was added dropwise to a pale yellow transparent sol and refluxed at 70-90℃ for 3-5 hours. In the later stage of the reaction, the pH rose to 5.5-6.0. The absorption peak at λ=360nm disappeared when the sample was monitored by UV-Vis, indicating that the reaction was complete and a ternary self-assembled catalyst was obtained.

[0024] In this invention, Al and Ti sources are first hydrolyzed with water in a solvent to generate intermediates containing hydroxyl groups (-OH). These intermediates then undergo condensation reactions to form Al-O-Ti, Al-O-Al, or Ti-O-Ti covalent bonds, gradually agglomerating into nanoscale particles and dispersing in a liquid to form a sol. The added coordination modifier stabilizes the metal ions through coordination, slowing down the hydrolysis rate (especially inhibiting aggregation caused by excessively rapid hydrolysis of the Ti source), ensuring uniform mixing of Al and Ti at the molecular scale. As the condensation reaction continues, the nanoparticles further crosslink to form a continuous three-dimensional network structure, encapsulating the liquid (such as alcohol or water) within the network pores. The system loses its fluidity and transforms into a gel. The weakly acidic environment of pH 4.2-4.8 in this invention inhibits excessively rapid particle growth.

[0025] Subsequently, a Pt source solution was added to introduce the Pt component into the pale yellow, transparent Al-Ti sol, where Pt exists as a coordination ion and Al... 3+ and Ti 4+ Hydrolysis-condensation forms hydroxylated nanoclusters with hydroxyl groups (-OH) and potential coordination modifiers on their surface. The overall structure is weakly acidic (pH 4.2-4.8), and the colloidal particles may carry a negative charge on their surface. This structure provides active sites for the binding of Pt ions. Specifically, if the Al-Ti sol particles are negatively charged and the Pt source is a positively charged complex, they bind rapidly through electrostatic attraction; if the Pt source is negatively charged, they may bind through incompletely hydrolyzed Al atoms in the sol. 3+ and Ti 4+ They are attracted and bound together by electrostatic attraction.

[0026] Coordination bonding: The hydroxyl groups in the Al-Ti sol and the oxygen atoms of the coordination modifier possess lone pairs of electrons, which can form coordination bonds (Pt-O bonds) with the empty d orbitals of Pt ions. This stabilizes the Pt ions on the surface or inside the Al-Ti nanoclusters, preventing the aggregation of free Pt ions. Subsequent reflux heating accelerates the further condensation of residual hydroxyl groups with Pt coordinated ions, allowing Pt to be covalently linked to the Al-Ti framework, forming a more stable ternary network structure. This structure physically isolates Pt in an aqueous environment while simultaneously transferring electrons to Pt through oxygen vacancies, reducing the d-band center and improving catalytic efficiency.

[0027] The Al source includes at least one of aluminum chlorides, aluminum nitrates, aluminum sulfates, aluminum oxides, and aluminum alkoxides; aluminum chlorides include, but are not limited to, AlCl3·6H2O (aluminum chloride hexahydrate) and AlCl3 (anhydrous aluminum chloride); aluminum nitrates include, but are not limited to, Al(NO3)3·9H2O (aluminum nitrate nonahydrate) and Al(NO3)3 (anhydrous aluminum nitrate); aluminum sulfates include, but are not limited to, Al2(SO4)3·18H2O (aluminum sulfate octadecahydrate) and Al2(SO4)3 (anhydrous aluminum sulfate); aluminum oxides include, but are not limited to, Al2O3 (aluminum oxide) and Al(OH)3 (aluminum hydroxide). Aluminum alkoxides include, but are not limited to, Al(O-iPr)3 (aluminum isopropoxide) and Al(OEt)3 (aluminum ethoxide). Preferably, the Al source is AlCl3·6H2O (AR, ≥99%) or Al(NO3)3·9H2O (AR, ≥99%).

[0028] The Ti source includes at least one of titanium chloride, titanium sulfate, titanium oxalate, titanium oxide, and titanium alkoxide; wherein, titanium chloride includes, but is not limited to, TiCl4 (titanium tetrachloride) or TiCl3 (titanium trichloride); titanium oxalate includes, but is not limited to, Ti(C2O4)2 (titanium oxalate); titanium sulfate includes, but is not limited to, Ti(SO4)2 (titanium sulfate); titanium oxide includes, but is not limited to, TiO2 (titanium dioxide) or Ti2O3 (titanium trioxide); titanium alkoxide includes, but is not limited to, tetrabutyl titanate (TBT), titanium isopropoxide (TTIP), ethyl titanate, or methyl titanate; preferably, the Ti source is tetrabutyl titanate TBT (≥98%, water content <0.05%) or titanium isopropoxide TTIP (≥98%).

[0029] Pt sources include at least one of platinum chloride, platinum oxide, platinum alkoxide, platinum complex, and platinum sulfate; Platinum chlorides include, but are not limited to, H₂PtCl₆·6H₂O (chloroplatinic acid hexahydrate), K₂PtCl₄ (potassium chloroplatinate), or PtCl₂ (platinum dichloride); platinum oxides include, but are not limited to, PtO₂ (platinum dioxide) or PtO (platinum monoxide); platinum alkoxides include, but are not limited to, Pt(O-iPr)₂ (platinum isopropoxide) or Pt(OEt)₂ (platinum ethanol); platinum complexes include, but are not limited to, [Pt(NH₃)₂Cl₂] (diamminedichloroplatinum) or [Pt(NH₃)₂Cl₂]·H₂O (diamminedichloroplatinum hydrate); platinum sulfates include, but are not limited to, PtSO₄ (platinum sulfate). Preferably, the Pt source is H₂PtCl₆·6H₂O (Pt content ≥ 37.5%) or K₂PtCl₄ (Pt content ≥ 46%).

[0030] The coordination modifier includes, but is not limited to, at least one of pyridine, triethylamine, ethylenediamine, hexamethylenetetramine, acetic acid, oxalic acid, benzoic acid, trifluoroacetic acid, ammonium chloride, potassium bromide, sodium iodide, water, methanol, ethylene glycol, acetylacetone, and 8-hydroxyquinoline; preferably, the coordination modifier is acetylacetone (acac, ≥99%) or 8-hydroxyquinoline (8-HQ, ≥99%), wherein acetylacetone is a β-diketone ligand with two oxygen atoms, which can form stable chelates with metal ions. It has strong coordination ability and can effectively stabilize metal ions, especially when forming complexes, increasing electron delocalization through resonance effects, thereby improving the stability of the complex. 8-hydroxyquinoline is a bidentate ligand that forms a stable chelate ring with metal ions through a phenoxy group (-OH) and a pyridine nitrogen atom (-N=). This bidentate coordination increases the stability and rigidity of the complex. Both react under mild conditions with significant steric hindrance.

[0031] Solvents include anhydrous ethanol (water content ≤ 0.2%).

[0032] Optionally, the present invention can also use surface modifiers to modify the surface of the ternary self-assembled catalyst. Since the ternary self-assembled catalyst needs to be mixed with other raw materials of the catalytic component and the raw materials of the matrix component, and these raw materials contain resin, better interfacial compatibility can be obtained through surface modification.

[0033] Specifically, the raw materials for the ternary self-assembled catalyst also include a surface modifier, and the preparation method of the ternary self-assembled catalyst further includes modifying the ternary self-assembled catalyst with the surface modifier, followed by removing the solvent to constant weight; the molar amount of the surface modifier is 14-16 times the molar amount of the total metal; preferably, the surface modifier includes, but is not limited to, at least one of KH550, KH560, mercaptosilane, tetraethyl orthosilicate, KH-570, and HMDZ. KH-570 (≥98%) is a preferred surface modifier.

[0034] Furthermore, this invention also provides a method for preparing the aforementioned dental impression silicone rubber material. The method is simple, comprising: mixing the raw materials of the matrix component to obtain a first mixture; mixing the raw materials of the catalytic component to obtain a second mixture; and mixing the first mixture and the second mixture to obtain the final product. Because the ternary self-assembled catalyst in this invention is pre-dispersed with hydrogen-containing silicone oil, it can be well mixed with other raw materials of the catalyst and also well mixed with the raw materials of the matrix component, ensuring uniform mixing of all raw materials.

[0035] The process of mixing the raw materials for the catalytic components includes: first, ultrasonically dispersing the ternary self-assembled catalyst with hydrogen-containing silicone oil, followed by vacuum degassing to obtain a catalytic dispersion; and then mixing the catalytic dispersion with vinyl silicone oil, reinforcing agent, filler and pigment in the catalytic components.

[0036] In this invention, the uniformity of the ternary self-assembled catalyst when mixed with other components is improved by pre-dispersing the ternary self-assembled catalyst with hydrogen-containing silicone oil. The hydrogen-containing silicone oil has a side-chain Si-H content of 0.4-0.6 wt% and a viscosity of 80-120 mPa·s at 25 °C. Preferably, the ultrasonic dispersion power is 500-900 W, the dispersion time is 20-60 min, and the ultrasonic dispersion is performed using a pulse mode of 4-6 s ultrasonic waves followed by 4-6 s pauses. Preferably, the viscosity of the catalyst dispersion is 110-130 mPa·s, and the particle size D50 is 25-35 nm.

[0037] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0038] Example 1 This embodiment provides a silicone rubber material for dental impressions, the raw materials of which include: (1) Matrix components: 90 parts vinyl silicone oil (5000 mPa·s), 10 parts vinyl MQ resin (4000 mPa·s), 3 parts hydrogen-containing silicone oil (2 wt% hydrogen content), 10 parts silica powder (D50=2 μm), and fumed silica (specific surface area 210 mm²). 2 2 parts of ( / g) and 0.3 parts of colorant (iron oxide).

[0039] (2) Catalytic components: 90 parts of vinyl silicone oil (5000 mPa·s), 10 parts of vinyl MQ resin (4000 mPa·s), 0.2 parts of ternary self-assembled catalyst (Al 500 ppm, Pt 200 ppm, Ti 1100 ppm), 10 parts of silica powder (D50=2 μm), and fumed silica (specific surface area 210 mm²). 2 2 parts of (g) and 0.2 parts of pigment (titanium dioxide).

[0040] Its preparation methods include: The raw materials of the matrix components are mixed to obtain the first mixture; the ternary self-assembled catalyst is first ultrasonically dispersed with hydrogen-containing silicone oil at 900W for 45 minutes (pulse mode 5 s on / 5 s off), followed by vacuum degassing for 10 minutes to obtain the catalytic dispersion; then the catalytic dispersion is mixed with vinyl silicone oil, reinforcing agent, filler and pigment in the catalytic components to obtain the second mixture; the first mixture and the second mixture are then mixed to obtain the final product.

[0041] The preparation methods for ternary self-assembled catalysts include: S1, precursor sol.

[0042] In a 250 mL three-necked flask under N2 protection, 2.41 g of AlCl3·6H2O (aluminum source) was weighed and dissolved in 100 mL of anhydrous ethanol. 3+ The concentration was 0.10 mol / L. 6.81 g of TBT (titanium source) and Ti were added. 4+ The concentration of the sol was 0.20 mol / L, at which point the Al:Ti molar ratio was 1:2. 6.01 g of acac was added, bringing the molar ratio (Al+Ti):acac = 1:2. The mixture was refluxed at 75 °C for 1.5 h to obtain a pale yellow, transparent sol with a pH of 4.2-4.8.

[0043] S2, in situ Pt complexation.

[0044] A 0.526 g (0.001 mol Pt) H₂PtCl₆·₆H₂O (platinum source) ethanol solution was added dropwise to the pale yellow transparent sol prepared in S1 over 30 min, maintaining a Pt:(Al+Ti) ratio of 1:30 (mol). The temperature was raised to 82°C and refluxed for 4 h; the pH rose to 5.5-6.0 in the later stage of the reaction. Samples were taken and monitored using UV-Vis (the disappearance of the absorption peak at λ = 360 nm indicates Pt). 4+ →Pt 2+ completely).

[0045] S3, Surface silanization.

[0046] Cool to 25°C, then add 0.497 g of KH-570 in one go (molar amount = total metal molar amount × 15.5). Continue stirring at 25°C for 24 h to obtain a translucent sol. Remove ethanol by rotary evaporation at 55°C and -0.09 MPa until constant weight is achieved.

[0047] Example 2 This embodiment is basically the same as Example 1, except that the composition of the ternary self-assembled catalyst in this embodiment is Al2O3 500 ppm, PtO2 100 ppm, and TiO2 1100 ppm.

[0048] The preparation method is basically the same as in Example 1, except that the Al source is replaced with Al(NO3)3·9H2O, the Ti source is replaced with TTIP, and the Pt source is replaced with PtO2 (the amount of Al source, Ti source and Pt source added is adjusted according to the content of the composition).

[0049] Example 3 This embodiment is basically the same as Example 1, except that the composition of the ternary self-assembled catalyst in this embodiment is Al 400 ppm + Al2O3 400 ppm, Pt 400 ppm, and Ti 800 ppm.

[0050] The preparation method is basically the same as in Example 1, except that Al is added in two steps: first, 0.364 g of AlCl3 is added, and then 0.320 g (20 nm) of Al2O3 nanoparticles are added. The rest is the same as in Example 1 (the amount of Al source, Ti source and Pt source added is adjusted according to the content of the composition).

[0051] Example 4 This embodiment is basically the same as Example 1, except that the composition of the ternary self-assembled catalyst in this embodiment is Al2O3 300 ppm + Al 500 ppm, PtO2 250 ppm, TiO2 900 ppm.

[0052] The preparation method is basically the same as in Example 1, except that the Pt source is PtO2, and the pH is adjusted to 5.0 with 0.1 mol / L HCl before sonication to dissolve the PtO2.

[0053] Example 5 This embodiment is basically the same as Example 1, except that the composition of the ternary self-assembled catalyst in this embodiment is Al 400 ppm + Al2O3 400 ppm, Ti 200 ppm + TiO2 900 ppm, Pt 500 ppm.

[0054] The preparation method is basically the same as in Example 1, except that the aluminum source is AlCl3·6H2O and Al(NO3)3·9H2O added in a 1:1 ratio, and the titanium source is TBT and TTIP added in a 1:1 ratio, only the amount of materials added is increased.

[0055] Example 6 This embodiment is basically the same as Embodiment 1, except that the composition of the ternary self-assembled catalyst in this embodiment is Al 600 ppm, Pt 300 ppm, and Ti 1000 ppm.

[0056] The preparation method is basically the same as in Example 1, except that it is carried out according to a 1 kg silicone rubber system; a 5 L double planetary mixer is used, and vacuum degassing is performed at -0.095 MPa.

[0057] Example 7 This embodiment is basically the same as Example 1, except that the composition of the ternary self-assembled catalyst in this embodiment is 900 ppm Al2O3, 200 ppm Ti + 900 ppm TiO2, and 500 ppm Pt.

[0058] The preparation method is basically the same as in Example 1, except that the aluminum source is changed to Al(NO3)3·9H2O, and the titanium source is a mixture of TBT and TTIP in a ratio of 2:5, with only the amount of feed increased.

[0059] Example 8 This embodiment is basically the same as Example 1, except that the composition of the ternary self-assembled catalyst in this embodiment is Al 600 ppm, Ti 800 ppm + TiO2 300 ppm, and PtO2 500 ppm.

[0060] The preparation method is basically the same as in Example 1, except that the aluminum source is changed to Al(NO3)3·9H2O, the titanium source is a mixture of TBT and TTIP in a ratio of 17:3, the platinum source is PtO2, and only the amount of feed is increased.

[0061] Comparative Example 1 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example has the following composition: Pt 600 ppm, Al and Ti 0.

[0062] Its preparation method includes: Pt nanosol (D 50 =5nm) directly dispersed in silicone oil.

[0063] Comparative Example 2 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example consists of 500 ppm Al2O3 + 1100 ppm TiO2, with 0 Pt.

[0064] The preparation method is the same as in Example 1, but the step of adding a Pt source is omitted.

[0065] Comparative Example 3 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example comprises: Al 500 ppm + Ti 1100 ppm + Pt 50 ppm, wherein the content of Pt is lower than the lower limit of this invention.

[0066] The preparation method is the same as in Example 1.

[0067] Comparative Example 4 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example consists of: Al 500 ppm + Pt 200 ppm.

[0068] The preparation method is the same as in Example 1, but the step of adding Ti source is omitted.

[0069] Comparative Example 5 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example consists of: Ti 1100 ppm + Pt 200 ppm.

[0070] The preparation method is the same as in Example 1, but the step of adding an Al source is omitted.

[0071] Comparative Example 6 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example consists of 500 ppm Al2O3 + 200 ppm Pt.

[0072] The preparation method is the same as in Example 1, but the step of adding Ti source is omitted.

[0073] Comparative Example 7 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example consists of: TiO2 1100 ppm + Pt 200 ppm.

[0074] The preparation method is the same as in Example 1, but the step of adding an Al source is omitted.

[0075] Comparative Example 8 This comparative example provides a silicone rubber material for dental impressions, the only difference being the catalyst. The catalyst in this comparative example consists of: Ti 1600 ppm + Pt 200 ppm.

[0076] The preparation method is the same as in Example 1, but the step of adding an Al source is omitted.

[0077] Comparative Example 9 This comparative example provides a silicone rubber material for dental impressions. The only difference is the preparation method of the catalyst. The composition of the catalyst in this comparative example is the same as that in Example 1, including: Al 500 ppm, Pt 200 ppm, and Ti 1100 ppm.

[0078] The preparation method of this comparative example differs from that of Example 1. In this comparative example, the Al source and Pt source are first coordinated, and then the Ti source is added. The specific operation steps are as follows: S1. In a 250 mL three-necked flask under N2 protection, weigh 2.41 g of AlCl3·6H2O (aluminum source) and dissolve it in 100 mL of anhydrous ethanol. 3+ The concentration was 0.10 mol / L. Add 0.526 g (0.001 mol Pt) of H₂PtCl₆·6H₂O (platinum source) ethanol solution. Add 6.01 g of aacac and reflux at 75 °C for 1.5 h.

[0079] S2, Add 6.81g of TBT (titanium source), Ti in the system 4+ The concentration was 0.20 mol / L, the molar ratio of Pt:(Al+Ti) = 1:30, and the reaction was refluxed at 82 °C for 4 h. The pH rose to 5.5-6.0 in the later stages of the reaction. Sampling was monitored using UV-Vis (the disappearance of the absorption peak at λ = 360 nm indicates Pt...). 4+ →Pt 2+ completely).

[0080] S3. Cool to 25°C and add 0.497g of KH-570 in one go. The molar amount is equal to the total molar amount of metal × 15.5. Continue stirring at 25°C for 24 h to obtain a translucent sol. Remove ethanol by rotary evaporation at 55°C and -0.09MPa until constant weight is achieved.

[0081] Experimental Example The samples provided in Examples 1-8 and Comparative Examples 1-9 were tested, and the test items and methods included: I. Curing Time (T) 90 ): Rheometer method (1) Test basis: The solidification form is determined by testing the viscosity change using a rheometer.

[0082] (2) Instruments and fixtures: Anton Paar MCR 302 rotational rheometer, PP25-AL (Φ=25 mm, stainless steel parallel plate), gap 1.0 mm.

[0083] (3) Environmental conditions: temperature 23 ± 1 °C; relative humidity 50 ± 5%; nitrogen atmosphere throughout the test to avoid moisture interference.

[0084] (4) Sample preparation: After manually mixing the catalytic component and the matrix component, immediately take 10-30 g and place it in the center of the lower plate of the rheometer, and close the mold to 1.0 mm.

[0085] (5) Test procedure: Strain scan: γ = 0.1–100 s⁻¹. Time scan: constant frequency f = 1 Hz, record the change of complex viscosity η* with time t. 90 Determination: The time when η* reaches 90% of its final plateau torque is defined as T. 90 The software automatically fits the data with an accuracy of ±0.1 min.

[0086] (6) Quality control: Each sample is measured three times in parallel and the average value is taken.

[0087] II. Pt ion release: ICP-MS method (1) Test basis: ISO 10993-12:2021 "Biological evaluation of medical devices - Part 12: Sample preparation and reference materials"; ASTM F1185-15 "Metal ion release test method"; GB / T 38735-2020 "Metal ion release test for oral medical devices".

[0088] (2) Instrument: Thermo iCAP RQ ICP-MS, equipped with PFA nebulization chamber and nickel sampling cone; internal standard Rh 10 μg / L.

[0089] (3) Extraction medium: artificial saliva (ISO / TR 10271 formula): NaCl 0.4 g / L, KCl 0.4 g / L, CaCl2·2H2O 0.795 g / L, NaH2PO4·2H2O 0.69 g / L, Na2S·9H2O 0.005 g / L, pH adjusted to 6.8±0.1 with NaOH.

[0090] (4) Sample preparation and extraction: The cured silicone rubber was made into circular discs with a diameter of Φ=10 mm and an altitude of 2 mm, and a surface area to volume ratio of 0.5 cm². 2 / mL. Each tablet was weighed (m=0.45 ± 0.01 g) and placed in a 50 mL polypropylene centrifuge tube. 20 mL of artificial saliva was added to completely submerge the tablet. The mixture was incubated at 37 ± 1 °C and 100 rpm for 72 h. 2 mL of the extract was collected at 6 h, 24 h, and 72 h, and the isothermal medium was immediately replenished.

[0091] (5) Pretreatment: The extract was filtered through a 0.22 μm filter membrane, then diluted 10 times with 2% HNO3, and Pt was directly determined by ICP-MS. 195 .

[0092] (6) Calculation and reporting: Pt release amount (μg / g) = (C × V) / m, where C is the detection concentration (μg / L), V is the extraction volume (L), and m is the sample mass (g).

[0093] (7) Quality control: Each batch includes blank, parallel, and spiked recovery (80-120%). The test report provides the cumulative release over 72 hours.

[0094] III. Cytotoxicity: ISO 10993-5:2009 MTT assay (1) Test basis: ISO 10993-5:2009 "Biological evaluation of medical devices - Part 5: In vitro cytotoxicity test"; GB / T 16886.5-2017.

[0095] (2) Sample extraction: Cut the cured silicone rubber into pieces <0.5 mm 3 Particles, in 6 cm 2 Immerse the extract in DMEM at a ratio of / mL for 37°C for 24 h. Filter the extract through a 0.22 μm filter to obtain a 100% stock solution, which is then diluted to 50% and 25% with culture medium.

[0096] (3) Perform cytotoxicity test: graded according to ISO 10993-5 Table 1: RGR≥80% is Grade 0-1, 50-79% is Grade 2, 30-49% is Grade 3, <30% is Grade 4.

[0097] (4) Result determination Examples 1–6: All RGR ≥ 90%, Grade 0–1; Comparative Example 1: RGR 68%, Grade 2; Comparative Example 3: RGR 85%, Grade 1.

[0098] IV. Data Statistics All values ​​are expressed as mean ± SD, n=3.

[0099]

[0100] As can be seen from the table above, in Examples 1-8 of this invention, ternary self-assembled catalysts were selected as catalysts for dental impression silicone rubber materials. When the effective content of Al in the ternary self-assembled catalyst is within the range of 500-900 ppm, the effective content of Pt is 100-500 ppm, and the effective content of Ti is 800-1100 ppm, regardless of whether it is elemental, oxide, or mixed form, T can be achieved. 90 ≤2.2min, 72 h Pt release ≤ 0.045 μg / g, cytotoxicity Grade 0-1.

[0101] Comparative Example 1 contained only Pt. While the curing time was relatively fast, the Pt release was more than 10 times higher, resulting in a cytotoxicity grade of 2. Comparative Example 2 lacked Pt, and Comparative Example 3 had too low a Pt content, neither meeting clinical curing requirements. Comparative Examples 4 and 6 omitted Ti, and Comparative Examples 5 and 7 omitted Al. It can be seen that using Al or Ti to load Pt can achieve good curing effects, but the Pt release is significantly higher than 10 times. The Pt release in Comparative Examples 5 and 7 is slightly lower than in Comparative Examples 4 and 6, demonstrating that Ti has a better sustained-release effect. Furthermore, the cytotoxicity of Comparative Examples 4-7 is all Grade 2. In Comparative Example 8, Al was omitted. When the Al content was supplemented with Ti, the excess Ti loaded Pt, resulting in faster curing. While the Pt content was within the range of this application, the Pt release was significantly lower than in Comparative Examples 4-7, but still higher than in Example 1. In Comparative Example 9, the preparation method was adjusted by first coordinating the Al source and the Pt source, and then adding the Ti source. At this time, it was found that the curing effect was significantly reduced. The reason is that Al failed to form an effective catalyst loading. The order of adding Al and Ti endows the three-way catalyst with a core-shell structure that enables effective catalyst release, thus limiting the release capacity of Pt.

[0102] In summary, the dental impression silicone rubber material provided by this invention utilizes a ternary self-assembled catalyst formed by the self-assembly of Al, Pt, and Ti as the catalyst component. The synergistic effect of Al, Pt, and Ti enables it to exhibit superior performance compared to single-metal or bimetallic catalysts in selective hydrogenation, CO oxidation, photocatalysis, and electrocatalysis. This invention uses an Al and Ti sol as a support to load Pt, with Pt covalently bonded to the Al-Ti framework, forming a stable ternary network structure. This structure physically isolates Pt in an aqueous environment while simultaneously transferring electrons to Pt through oxygen vacancies, reducing the d-band center and improving catalytic efficiency. This invention can significantly reduce Pt ion release and cytotoxicity while maintaining or shortening the curing time.

[0103] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A silicone rubber material for dental impressions, characterized in that, Its raw materials include a matrix component and a catalytic component in a mass ratio of 1:0.8-1.

2. The catalytic component contains a ternary self-assembled catalyst. The effective content of Al in the ternary self-assembled catalyst is 500-900 ppm, the effective content of Pt is 100-500 ppm, and the effective content of Ti is 800-1100 ppm.

2. The dental impression silicone rubber material according to claim 1, characterized in that, The raw materials of the ternary self-assembled catalyst include an Al source, a Ti source, a Pt source, a coordination modifier, and a solvent. The molar ratio of Al to Ti in the Al source and the Ti source is 1:1-3. The molar ratio of the total molar amount of Al and Ti in the Al source and the Ti source to the molar amount of the coordination modifier is 1:1-3. The molar ratio of Pt in the Pt source to the total molar amount of Al and Ti in the Al source and the Ti source is 1:10-50.

3. The silicone rubber material for dental impressions according to claim 2, characterized in that, The Al source includes at least one of aluminum chloride, aluminum nitrate, aluminum sulfate, aluminum oxide, and aluminum alkoxide. And / or, the Ti source includes at least one of titanium chloride, titanium sulfate, titanium oxalate, titanium oxide and titanium alkoxide; And / or, the Pt source includes at least one of platinum chloride, platinum oxide, platinum alkoxide, platinum complex, and platinum sulfate; And / or, the coordination modifier comprises at least one of pyridine, triethylamine, ethylenediamine, hexamethylenetetramine, acetic acid, oxalic acid, benzoic acid, trifluoroacetic acid, ammonium chloride, potassium bromide, sodium iodide, water, methanol, ethylene glycol, acetylacetone, and 8-hydroxyquinoline; And / or, the solvent includes anhydrous ethanol.

4. The silicone rubber material for dental impressions according to claim 2, characterized in that, The preparation method of the ternary self-assembled catalyst includes: The Al source and the Ti source are dissolved in the solvent in a molar ratio to form a mixed solution with a concentration of 0.05-0.15 mol / L. The coordination modifier is added in a molar ratio, and the mixture is refluxed at 60-80℃ for 1-3 hours to obtain a pale yellow transparent sol with a pH of 4.2-4.

8. The Pt source is dissolved in the solvent to form a Pt source solution with a concentration of 0.01-0.03 mol / L. The Pt source solution is added dropwise to the pale yellow transparent sol and refluxed at 70-90℃ for 3-5 hours. In the later stage of the reaction, the pH rises to 5.5-6.

0. The absorption peak at λ=360nm disappears when the sample is monitored by UV-Vis, indicating that the reaction is complete, and the ternary self-assembled catalyst is obtained.

5. The dental impression silicone rubber material according to claim 4, characterized in that, The raw materials for the ternary self-assembled catalyst also include a surface modifier, and the preparation method of the ternary self-assembled catalyst further includes modifying the ternary self-assembled catalyst with the surface modifier, and then removing the solvent to constant weight; Preferably, the molar amount of the surface modifier is 14-16 times the molar amount of the total metal; Preferably, the surface modifier includes at least one of KH550, KH560, mercaptosilane, tetraethyl orthosilicate, KH-570, and HMDZ.

6. The silicone rubber material for dental impressions according to claim 1, characterized in that, The raw materials of the matrix component, by weight, include 80-100 parts of vinyl silicone oil, 8-12 parts of reinforcing agent, 2-4 parts of hydrogen-containing silicone oil, 10-15 parts of filler, and 0.1-0.5 parts of pigment; the raw materials of the catalytic component, by weight, include 80-100 parts of vinyl silicone oil, 8-12 parts of reinforcing agent, 2-4 parts of hydrogen-containing silicone oil, 0.1-0.3 parts of ternary self-assembled catalyst, 10-15 parts of filler, and 0.1-0.5 parts of pigment.

7. The dental impression silicone rubber material according to claim 6, characterized in that, The viscosity of the vinyl silicone oil in the matrix component and the catalytic component is 1000-10000 mPa·s, preferably 3000-8000 mPa·s, and the vinyl content is 0.02-2 wt.%. And / or, the reinforcing agent in both the matrix component and the catalytic component comprises at least one of methyl vinyl MQ silicone resin and vinyl MQ silicone resin, wherein M is a monofunctional Si-O unit, Q is a tetrafunctional Si-O unit, the M / Q ratio is between 0.8 and 1.2, the reinforcing agent has a viscosity of 100-10000 Pa·s at room temperature, and a vinyl content of 0.1-5 wt.%. And / or, the hydrogen content of the hydrogen-containing silicone oil is 0.1-5 wt%, preferably 0.1-2 wt%; And / or, the filler in the matrix component and the catalyst component is a mixture of silica powder and fumed silica; And / or, the pigments in the matrix component and the catalytic component are at least one of iron oxide and titanium dioxide.

8. The dental impression silicone rubber material according to claim 7, characterized in that, The particle size of the silicon micro powder is 1-10 μm, preferably 2-6 μm; And / or, the specific surface area of ​​the fumed silica is greater than 200 mm². 2 / g; And / or, the mass ratio of the silicon micropowder to the fumed silica is 5-50:1, preferably 5-30:

1.

9. The method for preparing the dental impression silicone rubber material according to any one of claims 1-8, characterized in that, It includes: mixing the raw materials of the matrix component to obtain a first mixture; mixing the raw materials of the catalytic component to obtain a second mixture; and mixing the first mixture and the second mixture to obtain the final product.

10. The method for preparing the dental impression silicone rubber material according to claim 9, characterized in that, Mixing the raw materials of the catalytic components includes: First, the ternary self-assembled catalyst is ultrasonically dispersed with hydrogen-containing silicone oil, followed by vacuum degassing to obtain a catalytic dispersion; then, the catalytic dispersion is mixed with the vinyl silicone oil, reinforcing agent, filler, and pigment in the catalytic component. Preferably, the side chain Si-H content of the hydrogen-containing silicone oil is 0.4-0.6 wt%, and the viscosity at 25 °C is 80-120 mPa·s; Preferably, the ultrasonic dispersion power is 500-900W, the dispersion time is 20-60min, and the ultrasonic dispersion is performed using a pulse mode of 4-6s ultrasonic waves followed by 4-6s pauses.